Empirical evidence has revealed cultural differences in the expression of aggressiveness. (European Journal of Education and Psychology, 2010)
The purpose of this study was to analyse aggressive behaviour differences among Spanish, Mexican and Chinese students of secondary education. The Antisocial Behaviour scale of the Teenage Inventory of Social Skills (TISS) was administered to 420 Spanish, 532 Mexican, and 431 Chinese, ranging from 12 to 15 years. Variance analyses showed that Chinese students presented significant higher levels of aggressiveness than Spanish and Mexican students. No differences were found among the last two groups. This pattern of results was similar by gender and age groups. Thus, all subsamples of Chinese students (boys, girls, 12-13 year olds, and 14-15 year olds) reported significant higher levels of aggressiveness than their Spanish and Mexican peers. However, differences found were of small and moderate magnitude. Results are discussed according to cultural dimensions of individualism vs. collectivism and power distance.